DIGITAL ANALYSIS AS A TOOL FOR IMPROVING THE DIGITAL ANALYSIS AS A TOOL FOR IMPROVING THE EFFICIENCY OF CORPORATE GOVERNANCE OF CORPORATE GOVERNANCE (Development Service Industry Management, 2025)
The article provides an in-depth study of the essence, significance, and development prospects of digital analysis as a tool for enhancing the efficiency of corporate governance in the context of digital transformation. The key areas of application of digital analytical technologies for ensuring the validity of management decisions, operational evaluation of performance, and comprehensive monitoring of key business processes are highlighted. It is substantiated that the integration of big data technologies, artificial intelligence, business intelligence (BI) systems, and interactive digital dashboards contributes to greater transparency of internal processes, strengthens adaptability to external changes, fosters strategic flexibility, and enhances the competitiveness of corporate structures.Special attention is given to the analysis of practical aspects of digital tools application in the activities of domestic companies, taking into account their sectoral specifics and the level of digital maturity. Examples of successful implementation of analytical solutions by Ukrainian enterprises are provided, demonstrating improvements in management processes due to digitalization. At the same time, key barriers hindering the active use of digital analysis in corporate environments are emphasized, including organizational, technological, financial, and human resource challenges. A set of recommendations is proposed to overcome these obstacles, such as increasing the digital competence of management staff, modernizing IT infrastructure, developing corporate digital strategies, and stimulating innovation.The results of the study confirm that the implementation of digital analysis is a critical condition for building a modern data-driven corporate governance system aimed at fast decision-making, risk forecasting, and ensuring sustainable development of enterprises in a dynamic business environment.
Keywords: digital analysis; corporate governance; digital technologies; big data; business analytics; strategic management; efficiency